ASSESSMENT OF C-REACTIVE PROTEINS IN RECENTLY DIAGNOSED TYPE-1 DIABETIC CHILDREN AS A RISK MARKER OF EARLY ATHEROSCLEROSIS - Hamad, Aqeela; Qureshi, Hamid Javaid; Roohi, Nabila (Journal of Ayub Medical College Abbottabad, 2014)
Background: Cardiovascular disease (CVD) is a leading cause of mortality and morbidity in diabetes mellitus (DM). Studies indicate that atherosclerosis has slowly altered from a model of chronic degenerative disease affecting patients with advanced ages to a model of subclinical chronic inflammatory disease present in childhood. DM is a risk factor for atherosclerosis and asymptomatic low grade inflammation occurs prior to unconcealed vascular lesions in these patients. A low grade inflammation can be determined by serum C-reactive protein (CRP). The aim of this study was to evaluate serum CRP levels in recently diagnosed type-1 diabetic children to predict early cardiovascular complications. Methods: In this cross-sectional study, serum CRP levels were determined in 39 diabetic children and 40 healthy children as control. CRP concentrations were determined by ELISA by an automated ELISA analyzer. The values were expressed as mean±standard deviation and data from patients and controls was compared by t-test. Results: Serum CRP levels were significantly elevated in diabetic children as compared to controls (p<0.001). Conclusion: Serum CRP can be used as a potent biochemical markers in addition to other traditional risk factors like dyslipidemia, hypertension, obesity and smoking to detect high risk patients. Keywords: CRP, type-1 diabetes, cardiovascular disease, inflammatory markers.